THE IMPACT OF AGRICULTURAL FIELD EXTENSION WORKERS' PERFORMANCE AND COMPETENCE ON FARMERS' SATISFACTION IN NEGERI BESAR DISTRICT, WAYKANAN REGENCY, WITH EXTENSION WORKERS' COMMITMENT AS A MODERATING VARIABLE - Hakim, Lukmanul; Adhi Pangeran Pangestu; M. Hasan Ma'ruf (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
The performance of field agricultural extension workers (PPL) is the ability of extension workers to carry out their main tasks which include providing education, information, and guidance to farmers, Currently the Agricultural Extension Unit of Negeri Besar District has as many as 12 Field Agricultural Extension Workers (PPL) with a total group of 132 farmer groups, with a total of 3,356 farmer group members, and an average of 1 farmer group of 25-30 people. This study was used to measure the level of satisfaction of farmers in assessing the performance of extension workers (X1) and the competence of extension workers (X2) with the seriousness of extension workers as a moderation variable. A quantitative approach was used by collecting data through questionnaires to 97 farmer groups. The validity test was carried out using the product moment correlation method and was carried out through the SPSS 25.0 application. The results of the analysis showed that the performance of extension workers did not have a significant effect on farmer satisfaction, the competence of extension workers had a significant effect on farmer satisfaction, the seriousness of extension workers strengthened the performance of extension workers, and the seriousness of extension workers strengthened employee competence. The results of the multiple regression correlation test showed that the R Square value of 0.746 showed that 74.6% of the variation in farmer satisfaction could be explained by a combination of independent variables. Overall, this regression model is quite strong and effective in explaining the influence of independent variables on farmer satisfaction in Negeri Besar District, Waykanan RegencyKeywords: Performance, Satisfaction, Seriousness.